Perancangan Interior Fasilitas Studio Program Studi Desain Interior Fakultas Seni dan Desain Universitas Kristen Petra - Andereas Pandu Setiawan, Klif Rumpuin (Intra, 2016)
Learning facilities is one of some means which are very needed by every university and faculties, especially at Petra Christian University. But mostly every facilities which provided by Petra Christian University is inadequate and less supportive for students activities and also for department for academic activities. The required facilities are design studio which support another supporting facilities. The activities undertaken are studying, designing, drawing, and assistance. Designing the studio facilities are based on learning experience, survey and location observation, interview, and location analysis that will be used, looking for design concept solution by making the prototype.Studio facilities are designed to fulfil students needs, and also creating an efficience and productive learning environment. Designing studio facilities is a one of the ways to fulfill Petra Christian Univerity students needs, in order to make them more comfortable in learning.